Entrepreneurship, Innovation Activities and Regional Growth - Aikaterini Kokkinou (European Regional Science Association (ERSA), 2005)
There is a huge literature for the role and the implications of entrepreneurship on innovation activities and economic growth, through 'regional systems of innovation'. This paper attempts to define the main determinant factors of entrepreneurial and innovation activities. In particular, the paper attempts to analyze, using an econometric approach, the effects of entrepreneurship on innovation activities and furthermore to clarify the implication on regional system of innovation, competitiveness, modernization process and regional growth.
Keywords: 330